2016
DOI: 10.1371/journal.pone.0167050
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Key Drivers of Return Reversal with Dynamical Bayesian Factor Graph

Abstract: In the stock market, return reversal occurs when investors sell overbought stocks and buy oversold stocks, reversing the stocks’ price trends. In this paper, we develop a new method to identify key drivers of return reversal by incorporating a comprehensive set of factors derived from different economic theories into one unified dynamical Bayesian factor graph. We then use the model to depict factor relationships and their dynamics, from which we make some interesting discoveries about the mechanism behind ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Earlier, Kang et al (2002) investigated all Chinese A stocks and reported that there is a short-term return reversal in Chinese A stock market, whereas other empirical studies claimed that future market returns are not dependent on the past performance. However, empirical research is not limited to finding the return reversal effect in stocks, i.e., Zhao et al (2016) explored the determinants of the return reversal and found liquidity as the most important that can cause return reversal effect. Naughton et al (2008) showed that there is a momentum effect in the Chinese stock market, whereas Li et al (2010) observed no such momentum effect in the Chinese market.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, Kang et al (2002) investigated all Chinese A stocks and reported that there is a short-term return reversal in Chinese A stock market, whereas other empirical studies claimed that future market returns are not dependent on the past performance. However, empirical research is not limited to finding the return reversal effect in stocks, i.e., Zhao et al (2016) explored the determinants of the return reversal and found liquidity as the most important that can cause return reversal effect. Naughton et al (2008) showed that there is a momentum effect in the Chinese stock market, whereas Li et al (2010) observed no such momentum effect in the Chinese market.…”
Section: Introductionmentioning
confidence: 99%